HUBUNGAN KEPATUHAN PERAWAT DALAM PERAWATAN KOLOSTOMI TERHADAP KEJADIAN INFEKSI POST OPERASI KANKER KOLOREKTAL DI MURNI TEGUH MEMORIAL HOSPITAL - Purba, Siti Ian Cariani; Banjarnahor, Seriga (STIKes Mitra Husada Medan, 2024)
The increase in the number of colostomy patients is proportional to the increase in the incidence of colorectal cancer, because almost all colorectal cancer patients have a colostomy. One of the side effects of a colostomy is the occurrence of infection, and this is thought to be due to the lack of adherence of nurses in colostomy care. This study aims to explain the relationship between nurses in colostomy care and the incidence of infection after colorectal cancer surgery. The population in this study were inpatient nurses at GB3A, 5West, GB2, and 3Asouth Murni Teguh Memorial Hospital, totaling 61 nurses. This type of research is quantitative research with a cross sectional design with the sampling technique in this study using random sampling analysis. The data results in this study using the Spearman Rank test show that there is a relationship between nurse compliance in colostomy care and the incidence of post-operative colorectal cancer infection at Murni Teguh Memorial Medan Hospital with a p-value < 0.05. It is recommended to conduct further research with a larger sample and add variables such as the influence of nurse compliance in colostomy care on the incidence of colorectal cancer infection.